AL-FUQAHA’ AL- SAB’AH; KEUNIKAN MANHAJ IJTIHAD DAN PENGARUHNYA TERHADAP THURUQ AL-ISTINBATH IMAM MALIK - Rahmat Hidayat (Universitas Islam Negeri Raden Fatah Palembang, 2021)
This article discusses the uniqueness of manhaj ijtihad al-fuqaha' al-sab'ah and its influence on Imam Malik's thuruq al-istinbath. Al-fuqaha' al-sab'ah are seven scholars of the tabi'in period who are even considered the pioneers of the Ahlu Hadith Madrasa. However, it turns out that their manhaj ijtihad is somewhat different from most ahl al hadith scholars. How is the uniqueness of manhaj ijtihad al-fuqaha' al-sab'ah, and its influence on Imam Malik's thuruq al-istinbath becomes a research question in this paper. The results showed that al-fuqaha' al-sab'ah still does not leave the characteristics of the ahl al-hadith scholars who adhere to the zahir al-Qur'an, the Sunnah of the Prophet, qaulu companions, and ijma' ahl Medina. When they don't find answers to problems, they use ra'yu. The use of ra'yu is accompanied by the use of the ijtihad method commonly used by ahl al-ra'yi scholars. This is where the